IMPACTO DA RESILIÊNCIA E DA AUTOEFICÁCIA SOBRE BURNOUT EM PROFISSIONAIS DE ENFERMAGEM - Loiola, Elainy da Silva Camilo (2015)
This study has sought to investigate the impact of resilience and self-efficacy on burnout in the nursing professionals. The resilience construct in the work s context refers to the form adaptation ability positive before the drawbacks happening in the working environment. Self-efficacy at work represents the individual s perception about his own competencies at performing tasks. The Burnout, on the other hand, is understood as a specific syndrome of the working environment as a consequence of occupational stress chronification, and presenting three dimensions: exhaustion, cynicism (depersonalization), and poor professional fulfillment. The sample to the research was made up by 82 nursing area workers from the Prompt-Service Units UPAs located in the state of Acre. Most participants are female in sex (78pc), 31 years old on average (DP=6.8). In order to measure the variables, the Resilience-at-Work, Self-Efficacy, and Burnout Characterization Scale were used, and for collecting the social-demographic data, a self-response quiz was used, which had been designed for this study. The data went through exploratory and descriptive analyses, variance analysis (ANOVA), Pesarson correlation analysis, and standard multiple linear regressions. Findings indicated that the nursing professionals presented average levels of resilience, self-efficacy and of the exhaustion and poor professional fulfillment of the burnout; and, in turn, low depersonalization level. Relationship was also found between self-efficacy at work and burnout, for the results suggested that there is correlation between self-efficacy and two out of the three burnout factors: emotional exhaustion and work let-down. Findings also revealed that resilience and self-efficacy, jointly, significantly predict towards the two burnout factors mentioned above. However, the variable responsible for such explanation was self-efficacy at work since it was the only one statistically significant to explain both reported burnout components. It is concluded that the professionals presenting higher resilience and self-efficacy levels are the ones being the least afflicted by burnout, such a devastating syndrome mercilessly attacking the professionals working to serve the people.